Strategia nierozstrzygalności w wierszu jest taki pomnik Tadeusza Różewicza - Mikołajczak, Małgorzata (Przestrzenie Teorii, 2019)
The article deals with Tadeusz Rożewicz’s poem jest taki pomnik and puts forward a new interpretation concerning the mechanisms he uses to construct meanings. The author focuses on three issues: (1) the role of photography as an interpreter, (2) intertextual encryption of key contexts for the spiritual idea of the poem, (3) the allopathic function of laughter. She also indicates components of the strategy of undecidability, as a result of which a work containing what might seem an unambiguous ideological statement launches mechanisms guarding against one-way reading.